Antecedents of halal Malaysia brand equity based on consumers’ explicit and implicit responses - Wan Ismail, Wan Rusni (2019)
Halal Malaysia brand does not represent a specific brand instead it can be found on various product packages due to its roles as the third party endorser. This has placed Halal Malaysia brand in the risk of equity dilution due to the sensitive nature of Halal issues to Muslim consumers and the volatility of manufacturers’ commitment towards maintaining Halal standard as required by JAKIM. However, the evidence on the effectiveness of Halal Malaysia is unclear as to date there are evidences that pointed out that this brand suffers from various setback including issues related to the negative publicities and brand recognition. For the purpose of this study evaluation of Halal Malaysia brand was carried out using customer based brand equity evaluation as it allows for the brand equity to be investigated from various perspectives. The current study was carried out using mixed method approach based on consumers explicit and implicit responses. Qualitative semi structured interview was carried out to determine consumer’s explicit response and quantitative research using implicit association test instrument was also carried out to determine Halal Malaysia equity based on consumer’s implicit association. Findings showed that consumers possessed fixed mindsets which influence how they evaluate Halal Malaysia brand. This has resulted that in certain products being perceived as low tolerance which makes Halal Malaysia cue on the products to be considered as negligible cues. Furthermore, these products also can potentially undermine the credibility of Halal Malaysia as consumers faced difficulties to associate these products with Halal, hence the presence of Halal Malaysia is viewed as either fake or JAKIM has involved in some sort of unlawful activity and awarded the endorsement illegally. Hence, it is crucial for Halal Malaysia brand proprietor to use a different approach in promoting this brand and the new direction should focuses on devising better strategies in the way information is disseminated which emphasizes more on educating consumers through brand knowledge.